The “windows”, scales, and bristles of the tropical moth Rothschildia lebeau (Lepidoptera: Saturniidae) - Hernández-Chavarría, Francisco (2004)
The common Spanish name of the moth Rothschildia lebeau (Saturniidae) is cuatro ventanas (four ‘windows’), because it exhibits a transparent oval path in each wing. The scales of the colored areas and the bristles from the “window” were analyzed. We developed a simple device to measure transmittance across the “windows” with an spectrophotometer. A square section of “window” was mounted onto a flat black card and placed onto a clamp that hung in the path of the light - beam of the spectrophotometer. Absorbance was measured at 350 and 550 nm, with the “window” positioned perpendicular to the light beam (incidence of 90°); then the measurements were repeated with the “window” moved at an angle of 45°. Each measurement was replicated 5 times. Wing color spots were analyzed with a light dissection microscope (stereoscope) and with scanning electron microscopy. The scales have a minimum of 4 morphological types, 3 of them showed the typical appearance of unspecialized scales described for other butterflies; whereas the fourth has features particular to this species. On the “window” the scales are transformed in hair-like bristles that do not interfere with light, conferring the transparency that characterizes the “windows”. However, if the wing is illuminated at an almost grazing-incidence, they reflect the light as a mirror. Two hypothetical functional explanation for the windows are mimicry and interspecies communication